DEVELOPMENT OF ALGORITHMS AND PROGRAMS FOR MULTI-CIRCUIT DIGITAL REGULATION OF AUTOMATED PROCESS CONTROL SYSTEMS - Khakimov Zafar Tulyaganovich; Rahmatov Doniyor Xudoyorovich; Olimbayev Otajon Azamat o’g’li; O’ng’arov Sardor Alisher o’g’li; Omonboyev Kamol Dilmurod o’g’li; O’ngarov Sardorbek Tursunboy o’g’li (Journals Park Publishing, 2022)
This paper considers the problem of automation of technological process control systems. Algorithm and programs of multiloop digital regulation of automated process control systems are developed. Three types of multiloop control systems are considered: combined, cascade and multiloop connected control systems. The results of the work can be used in the development of industrial systems of digital regulation.
Keywords: automation; control system; digital